A vector autoregression (VAR) analysis of corruption, economic growth, and foreign direct investment in Ghana - Randolph Nsor-Ambala; Ebenezer Bugri Anarfo (Cogent Economics & Finance)
The paper investigated the dynamic and causal relationship among corruption, foreign direct investment, and economic growth simultaneously, a largely overlooked area in empirical studies, using a dataset from Ghana. It is among the few studies that explore the confluence of these variables and therefore contributes to understanding the contextual realities of the impact of FDI inflow, an often-prioritised policy choice, on widely used measures of social coherence and welfare. The study employed a vector autoregressive (VAR) estimation approach to empirically explore the relationships among corruption, foreign direct investment, and economic growth. The findings suggest that there is a reverse causality among corruption, foreign direct investment, and economic growth. This indicates that these variables are complementary rather than contradictory. These findings imply that central government and policymakers should not pursue any of these variables as a policy goal, but rather treat them as complements when modelling or formulating economic policies. This means that policies aimed at promoting foreign direct investment will not jeopardize or compromise the control of corruption and economic growth and vice versa.